Os Desafios Da Geografia Física Na Fronteira Do Conhecimento 2017
DOI: 10.20396/sbgfa.v1i2017.2008
|View full text |Cite
|
Sign up to set email alerts
|

O ensino de solos no curso de licenciatura em geografia: análise curricular do extremo sul do Rio Grande do Sul

Abstract: Este trabalho discute as diferentes abordagens da Ciência do Solo e verifica se o conhecimento adquirido pelos formandos em Licenciatura em Geografia da UFPel atende ao previsto nos PCN's e nos livros didáticos do Ensino Fundamental -Anos Finais, especificamente a Coleção Projeto Araribá, disponíveis nas escolas de Pelotas/RS. Com base no previsto nesses documentos foram elencadas temáticas relacionados à Ciência do Solo abordadas no Ensino Fundamental. Elaborouse um questionário acerca dos solos, aplicado aos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…As an example, the work developed by Laine (2003) estimated the bulk density for a nickel deposit by applying the kriging technique and revealed that the use of averages densities in the deposit studied led to an underestimation of the amount of metal. Similar approach can be found in the work developed by Madani and Mohammadi (1996) for a barite deposit, Dias (2012) in a copper deposit and Lisboa (2018) in an iron deposit.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…As an example, the work developed by Laine (2003) estimated the bulk density for a nickel deposit by applying the kriging technique and revealed that the use of averages densities in the deposit studied led to an underestimation of the amount of metal. Similar approach can be found in the work developed by Madani and Mohammadi (1996) for a barite deposit, Dias (2012) in a copper deposit and Lisboa (2018) in an iron deposit.…”
Section: Introductionsupporting
confidence: 56%
“…However, the cokriging technique can also be used to estimate the bulk density in a block model (Salinas and Emery 2012). According to Dias (2012), this procedure is used for situations in which the density is not sampled at all points where the attribute of interest was sampled (heterotopic database), and a correlation between this attribute and the density exists.…”
Section: Introductionmentioning
confidence: 99%